2020
DOI: 10.1021/acscatal.0c02454
|View full text |Cite
|
Sign up to set email alerts
|

P/N Heteroleptic Cu(I)-Photosensitizer-Catalyzed Deoxygenative Radical Alkylation of Aromatic Alkynes with Alkyl Aldehydes Using Dipropylamine as a Traceless Linker Agent

Abstract: A deoxygenative radical alkylation of aromatic alkynes with alkyl aldehydes for the preparation of allylarenes has been successfully achieved. This transformation is accomplished through the reaction of alkyl aldehydes with alkynes in the presence of dipropylamine and Hantzsch ester catalyzed by a P/N heteroleptic Cu­(I)-based photosensitizer under photoredox catalysis conditions. Preliminary mechanistic studies reveal that this aldehyde–alkyne coupling process comprises a regioselective radical addition of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 155 publications
(66 reference statements)
0
16
0
Order By: Relevance
“…The first step in typical photocatalytic cycles is the excitation of a photosensitizer by the absorption of a photon. , While traditionally applied, photosensitizers are often based on noble 4d and 5d metals, especially those with a low-spin d 6 configuration. , Research is currently aiming to overcome these rare and expensive metals. To achieve this goal, photocatalytic systems are being developed, that rely on organic chromophores , or more abundant 3d metals. Especially heteroleptic Cu­(I) complexes, consisting of a diphosphine and a diimine ligand, can combine the key properties of long excited state lifetimes and high quantum yields. , They also demonstrated their capacity to outperform their Ir­(III)- and Ru­(II)-based competitors in certain photocatalytic applications. …”
Section: Introductionmentioning
confidence: 99%
“…The first step in typical photocatalytic cycles is the excitation of a photosensitizer by the absorption of a photon. , While traditionally applied, photosensitizers are often based on noble 4d and 5d metals, especially those with a low-spin d 6 configuration. , Research is currently aiming to overcome these rare and expensive metals. To achieve this goal, photocatalytic systems are being developed, that rely on organic chromophores , or more abundant 3d metals. Especially heteroleptic Cu­(I) complexes, consisting of a diphosphine and a diimine ligand, can combine the key properties of long excited state lifetimes and high quantum yields. , They also demonstrated their capacity to outperform their Ir­(III)- and Ru­(II)-based competitors in certain photocatalytic applications. …”
Section: Introductionmentioning
confidence: 99%
“…In this area, copper complexes represent the most attractive and promising alternative candidates . Indeed, over the past two decades, there have been increasingly more reports about the copper-based photoactive complexes and their applications in visible-light-driven organic synthesis. Despite the impressive progress, it is still highly desirable to develop novel and efficient organic transformations involving the direct use of copper-based photosensitizers under visible-light-driven catalysis conditions.…”
mentioning
confidence: 99%
“…Deuterium enrichment of 35% at the 3-position of azetidine was possibly due to copper-assisted deuteration of acetylene-hydrogen under basic conditions. 56 This was further supported by the control experiment. In the presence of 2 equiv of D 2 O, substrate 8 was isolated with a D enrichment rate of 94% ( Figure 4 C).…”
Section: Resultsmentioning
confidence: 59%
“…When Et 3 N (2 equiv) was used as the reducing and reacting agent, we obtained allylbenzene 3a as the major product (75%) (entry 12, Figure 2 ). 57 , 56 Through systematic screening, we found that when acetonitrile was used as the solvent, the amine to alkyne ratio was crucial for obtaining 3a (entries 10 and 11, Figure 2 ). Control experiments showed that the photosensitizer and light were essential for double functionalization (entry 14, Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation